Impacts of transport connections on port hinterlands. Issue 4 (3rd April 2019) - Guerrero, David
ABSTRACT: This paper examines the spatial distribution of freight flows between the French NUTS-3 regions and West European ports. It focuses on the impacts of the quality of inland and maritime connections on the scope of hinterlands. The results of a spatial interaction analysis reveal that the inland distance constraint is significantly lower when intermodal connections such as regular barge or rail services are available. A case study focused on East Asian trade confirmed that factors related to maritime connectivity, such as the frequency of services at ports and their ability to accommodate large vessels, also contribute to limit the distance impedance. However, these effects vary considerably depending on the value density of the cargo.